3D geophysical mapping of the subsurface to support urban water planning: a case study from Simawa, Nigeria. Issue 1 (31st December 2022) - Fadakinte, Ifedayo
ABSTRACT: Simawa town, Ogun state, lacks the required water infrastructure for rapid urban development. This study seeks to use the geoelectric method – taking into account the geology and hydrogeology of the study area – to determine the groundwater potential of the town. Fifteen Vertical Electrical Sounding (VES) stations were spread across the town to characterise the subsurface layers. Interpretation of the VES data yielded five geoelectric layers. A lithology log from a prior borehole was used as a geologic control to confirm the validity of the VES results. The five geoelectric layers correspond to the topsoil (layer 1), Akinbo clay (layer 2), Akinbo shale (Layer 3), Ewekoro limestone (Layer 4), and Abeokuta sandstone (layer 5). The Abeokuta sandstone represents the main aquifer unit, a confined aquifer that can serve as a suitable source of potable water. Boreholes drilled in Simawa town should target the confined sandstone aquifer at a minimum depth of 80 m.